Response of Beef Cattle Farmers to The Presence of Farmer Groups in South Parigi District, Parigi Moutong Regency, Central Sulawesi - Basyarewan, Eko Saputra N.; Handayani, Sayekti; Riandhana, Taufiq Eka (Jurnal Sains dan Teknologi Peternakan, 2024)
Livestock farming is a significant sub-sector of agriculture with substantial potential for development. Within this sub-sector, beef cattle farming stands out as a particularly promising enterprise. In South Parigi District, Parigi Moutong Regency, the presence of beef cattle farmer groups plays a crucial role in enhancing livestock productivity and quality. This study aims to ascertain the responses of beef cattle farmers and to evaluate the influence of age, education, and farming experience on these responses towards the presence of farmer groups in South Parigi District, Parigi Moutong Regency. This descriptive quantitative study used snowball sampling to select 32 samples. Data collection was conducted through observation, interviews, and documentation. The collected data were then analyzed using multiple linear regression statistical analysis. The results indicated that the majority of responses were categorized as high (20 respondents, 55.6 %), followed by medium (15 respondents, 41.7 %), and low (1 respondent, 2.8 %). The analysis revealed significant p-values for age (0.046), education level (0.012), and farming experience (0.031), indicating significant relationships between these factors and the responses of beef cattle farmers.